2022
DOI: 10.1039/d2tb00798c
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-grafted porcine pericardium by copolymerization to improve the cytocompatibility, hemocompatibility and anti-calcification properties of bioprosthetic heart valve materials

Abstract: Bioprosthetic heart valves (BHVs) have been used widely due to the development of transcatheter heart valve replacement technology. However, glutaraldehyde crosslinked pericardium (GA), which is widely used as a leaflet...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Inflammatory reaction is an important cause of thrombosis and failure of implantation in vascular stents. 20,21,58,59 7 days after implantation, all experimental groups and the control group showed certain inflammatory cell infiltration as shown in Fig. 8, which was mainly caused by the trauma during the operation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Inflammatory reaction is an important cause of thrombosis and failure of implantation in vascular stents. 20,21,58,59 7 days after implantation, all experimental groups and the control group showed certain inflammatory cell infiltration as shown in Fig. 8, which was mainly caused by the trauma during the operation.…”
Section: Resultsmentioning
confidence: 97%
“…18,19 Many studies have been devoted to improving the hydrophilicity of the surface and form a hydrated layer on the stents to inhibit the adhesion and activation of platelets. [20][21][22] Meanwhile, achieving the adhesion and growth of endothelial cells on the surface of stent materials is also an effective method to inhibit thrombosis, especially for the middle and late stage of implantation. 23,24 Some hydrophilic polymers, including tertiary amines such as N,Ndimethylaminopropyl acrylamide (DMAPAA) have been used in the surface modification of blood contact materials to enhance blood compatibility via promoting the growth of human umbilical vein endothelial cells (HUVECs) and inhibiting the activation of the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%
“…动物源胶原填充剂 可以促进胶原再生实现皮肤年轻化 , 然而, 稳定性 差、在体内易降解, 限制其临床应用 [21,22] . 交联剂可 以提高胶原填充剂的稳定性, 如戊二醛 (GA), 但它 们的广泛应用受到细胞毒性和诱导组织钙化的影响 [23][24][25][26] . 因此, 开发长效的、生物相容性好的胶原蛋白 填充剂至关重要.…”
Section: 有增加胶原生成的潜力 但在注射后容易出现肿块unclassified
“…The results showed that this treatment not only enhanced the mechanical properties of the decellularized porcine heart valves but also avoided the cytotoxicity from glutaraldehyde, and the oxidized alginate-treated BHVs exhibited excellent biocompatibility and anti-calcification potential (Figure 7). [155] Similarly, not only alginate but also polymeric compounds such as extracellular matrix, [191] hyaluronic acid, [192] and amino acids [193] extracted from animal skin exhibit excellent anti-inflammatory properties due to their good biocompatibility.…”
Section: Surface Modification Of Natural Polymeric Materials To Impro...mentioning
confidence: 99%